Opportunities for Simulation in Software Engineering - França, Breno Bernard Nicolau de; Graciano Neto, Valdemar Vicente (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS), 2021)
Simulation has been successfully used in several domains, for research and practical purposes. Systematic approaches for simulation arose and a myriad of simulation models were proposed in the context of Software Engineering over the past decades. Despite the lack of rigor and industrial relevance on many of these, we discuss the existing synergies and consolidated knowledge to foster new opportunities between these areas.